An Exploratory Study Investigating the Effects of a Treatment Manual for Video Game Addiction. Issue 2 (October 2015) - Pallesen, Ståle; Lorvik, Ingjerd Meen; Bu, Eli Hellandsjø; Molde, Helge
This study investigated the effects of a manualized therapy for video game addiction in 12 males, ages 14–18 yr. The manual was based on cognitive-behavioral therapy, short-term strategic family therapy, solution-focused therapy, and motivational interviewing. Treatment response was reported by the patients, their mothers, and the therapists. The patients reported moderate (but statistically non-significant) improvement from pre- to post-treatment. The mothers, however, reported large effects and statistically significant improvement from pre- to post-treatment. The therapists reported marked or moderate treatment response in six of the 12 patients. The ratings of change by mothers converged well with the views of change of both the patients and therapists, whereas the convergence of views on change between the two latter sources was far lower.